2022
DOI: 10.4103/jfmpc.jfmpc_1802_21
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge and attitude towards prostate cancer and screening practices among males in Saudi Arabia

Abstract: Background: Early-stage prostate cancer can be asymptomatic. The digital rectal exam (DRE) and the prostate specific antigen (PSA) test are usually used for prostate cancer screening. This study aims to assess knowledge and attitudes towards prostate cancer screening among males in Saudi Arabia. Materials and Methods: A cross-sectional study was conducted on Saudi males above the age of 40. A self-reported questionnaire was distributed online. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Family history, advanced age, and race/ethnicity (ie, African ancestry) are among the known risk factors for Pca [ 36 ]. Approximately one-half of participants (51.65 %) knew at least one risk factor for Pca; of these, 50 % identified advanced age as a risk factor, which is consistent with previous studies that noted significant awareness of age as a risk factor [ [37] , [38] , [39] , [40] ]. However, lower levels of awareness of advanced age as a risk factor have been found in Uganda and elsewhere [ 18 , 35 , 41 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Family history, advanced age, and race/ethnicity (ie, African ancestry) are among the known risk factors for Pca [ 36 ]. Approximately one-half of participants (51.65 %) knew at least one risk factor for Pca; of these, 50 % identified advanced age as a risk factor, which is consistent with previous studies that noted significant awareness of age as a risk factor [ [37] , [38] , [39] , [40] ]. However, lower levels of awareness of advanced age as a risk factor have been found in Uganda and elsewhere [ 18 , 35 , 41 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, 35.1 % of South African men reported knowing that family history is a risk factor for Pca development [ 41 ]. In addition, Alothman et al, in a Saudi Arabian study, reported up to 46 % of participants had identified family history as a risk factor [ 40 ]. These finding contradict our present results, in which only 0.6 % and 0.9 % of participants identified genetic/familial factors and race respectively as risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The male genitalia includes a tiny accessory gland located close to the lower part of the bladder known as the prostate gland, which undergoes malignant changes in prostate cancer. Proteolytic enzymes are released by the prostate, which weighs around 20 g, into the sperm to aid in fertilization [1]. Prostate cancer presents with physical and psychological symptoms that distinguish it.…”
Section: Introductionmentioning
confidence: 99%